Formalizing shape-change: Three-dimensional printed shapes and hygroscopic material transformations. (March 2020) - Vazquez, Elena; Gürsoy, Benay; Duarte, Jose Pinto
Shape-changing materials have become increasingly popular among architects in designing responsive systems. One of the greatest challenges of designing with these materials is their dynamic nature, which requires architects to design with the fourth dimension, time. This article presents a study that formalizes the shape-changing behavior of three-dimensional printed wood-based composite materials and the rules that serve to compute their shape-change in response to variations in relative humidity. In this research, we first developed custom three-dimensional printing protocols and analyzed the effects of three-dimensional printing parameters on shape-change. We thereafter three-dimensional printed kirigami geometries to amplify hygroscopic material transformation of wood-based composites.